2002
DOI: 10.1016/s0014-5793(02)02974-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for alteration of unfolding profile of a helical peptide by far‐ultraviolet circular dichroism aromatic side‐chain contribution

Abstract: Aromatic side-chains are known to contribute to the far-UV circular dichroism (CD) spectra of peptides and proteins. Among other things, this can signi¢cantly a¡ect the measured helix propensities of amino acids [Chakrabartty et al., Biochemistry 32 (1993) 5560^5565]. In order to address how interfering side-chain contributions can a¡ect the backbone unfolding transition of a helical peptide, as monitored by [a a] 222 (molar ellipticity at 222 nm), we have studied the unfolding transition of a short designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Typically Tyr is introduced in a synthetic peptide for accurate concentration measurement. MD results showed that Tyr side chain could affect the inherent helical propensities of the designed backbone, confirming our earlier experimental study 28…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Typically Tyr is introduced in a synthetic peptide for accurate concentration measurement. MD results showed that Tyr side chain could affect the inherent helical propensities of the designed backbone, confirming our earlier experimental study 28…”
Section: Resultssupporting
confidence: 88%
“…The synthesis, purification and characterization of the peptides studied, ABK (Ac‐Ala‐Aib‐Ala‐Lys‐Ala‐Aib‐Lys‐Ala‐Lys‐Ala‐Aib‐Tyr‐NH 2 ) and ABGY (Ac‐Ala‐Aib‐Ala‐Lys‐Ala‐Aib‐Lys‐Ala‐Lys‐Ala‐Aib‐Gly‐Gly‐Tyr‐NH 2 ), have been reported earlier 28, 29. The peptides contain 42% Ala with a strong preference for the α‐helical backbone, 25% Aib (single letter code: B) with a strong preference for the 3 10 ‐helix making them ideal candidates for exhibiting the α/3 10 ‐helix transition.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The shapes of the CD spectra of the peptides (Supporting Information Fig. S3), K7 (Ac‐A EPYAS BKBAKA‐NH 2 ) and K8 (Ac‐A EPYAS BAKBKAA‐NH 2 ), were similar to the CD spectra of ABK (Ac‐ABAKABKAKABY‐NH 2 ) and ABGY (Ac‐ABAKABKAKABGGY‐NH 2 ), two helical peptides containing Ala/Aib of similar length . However, the CD band intensities of K7 and K8 were reduced by ∼50%, not unexpected because of the higher Ala/Aib content in ABK/ABGY and the presence of Pro in K7 and K8.…”
Section: Resultsmentioning
confidence: 81%